세계 곡물시장의 현황과 전망 - 이태호 (한국농촌경제연구원, 2007)
Recently, world grain prices show highly unstable behavior. During the period of 2002-2006, prices of corn, soybean, wheat went up about 50%. Among the five major grains (rice, wheat, corn, barley, soybean), corn and soybean are the most vulnerable to international price fluctuations. The world market demand for corn and soybean increases rapidly with increasing meat consumption in China and India that have huge populations but unstable booming economies. The demand for corn and soybean as raw materials for bio-fuel increases at a fast pace due to the growing international concerns about global warming. But the economic efficiency of bio-fuel is still controversial. Furthermore, the supply of corn and soybean in the international market is dominated by a small number of countries - mainly USA, Brazil and Argentina. However, the instability of corn and soybean prices would not last so long because of the following reasons. The first is new developments in life sciences such as a bio-fuel technology that extracts alcohol from cellulose or GM (genetic modification) technologies that enhance the efficiency in grain production. The second is the globalization of free market economy that makes the world grain market stabilized by the invisible hand. The third is the long term downward trend of the grain prices in USA that is the world largest exporter of corn and soybean. Except the brief surges in 1940's, 1970's and early 2000's, the corn and soybean prices of USA has never shown a significant sign of rise. Even though it would not last long, the price instability in international feed grain market could cause serious damage in Korean pork market and hog industry that are already experiencing many troubles caused by open market policies. Hence it is necessary for the government to take policy measures to stabilize the pork market and hog industry. Researchers: Tae-ho, Lee and Han-ho, Kim Research period: 2007.07~2007.09 E-mail address: aglee@snu.ac.kr, hanho@snu.ac.kr